Welcome to Westonci.ca, the place where your questions are answered by a community of knowledgeable contributors. Discover detailed answers to your questions from a wide network of experts on our comprehensive Q&A platform. Get detailed and accurate answers to your questions from a dedicated community of experts on our Q&A platform.
Sagot :
To graph the rational function [tex]\( f(x) = \frac{2}{-x-2} \)[/tex], follow these steps:
### Step 1: Determine the Vertical Asymptote
The vertical asymptote occurs where the denominator is zero. Here, the denominator is [tex]\(-x-2\)[/tex]. Setting this equal to zero and solving for [tex]\( x \)[/tex]:
[tex]\[ -x - 2 = 0 \][/tex]
[tex]\[ -x = 2 \][/tex]
[tex]\[ x = -2 \][/tex]
So, the vertical asymptote is at [tex]\( x = -2 \)[/tex].
### Step 2: Determine the Horizontal Asymptote
For large values of [tex]\( x \)[/tex], the rational function [tex]\( f(x) \)[/tex] approaches a horizontal asymptote. As [tex]\( x \)[/tex] approaches either positive or negative infinity, the term [tex]\(-x - 2\)[/tex] grows large in magnitude, and thus [tex]\( f(x) \)[/tex] approaches zero. Hence, the horizontal asymptote is:
[tex]\[ y = 0 \][/tex]
### Step 3: Plot Points Around the Vertical Asymptote
To understand the behavior of the function around the vertical asymptote, we will plot points on either side of [tex]\( x = -2 \)[/tex].
1. Points to the left of [tex]\( x = -2 \)[/tex]:
- For [tex]\( x = -3 \)[/tex]:
[tex]\[ f(-3) = \frac{2}{-(-3) - 2} = \frac{2}{3 - 2} = \frac{2}{1} = 2 \][/tex]
So the point is [tex]\((-3, 2)\)[/tex].
- For [tex]\( x = -4 \)[/tex]:
[tex]\[ f(-4) = \frac{2}{-(-4) - 2} = \frac{2}{4 - 2} = \frac{2}{2} = 1 \][/tex]
So the point is [tex]\((-4, 1)\)[/tex].
2. Points to the right of [tex]\( x = -2 \)[/tex]:
- For [tex]\( x = -1 \)[/tex]:
[tex]\[ f(-1) = \frac{2}{-(-1) - 2} = \frac{2}{1 - 2} = \frac{2}{-1} = -2 \][/tex]
So the point is [tex]\((-1, -2)\)[/tex].
- For [tex]\( x = 0 \)[/tex]:
[tex]\[ f(0) = \frac{2}{-0 - 2} = \frac{2}{-2} = -1 \][/tex]
So the point is [tex]\((0, -1)\)[/tex].
### Step 4: Draw the Graph
1. Draw the vertical asymptote as a dashed line at [tex]\( x = -2 \)[/tex].
2. Draw the horizontal asymptote as a dashed line at [tex]\( y = 0 \)[/tex].
3. Plot the points [tex]\((-3, 2)\)[/tex] and [tex]\((-4, 1)\)[/tex] to the left of [tex]\( x = -2 \)[/tex].
4. Plot the points [tex]\((-1, -2)\)[/tex] and [tex]\((0, -1)\)[/tex] to the right of [tex]\( x = -2 \)[/tex].
5. Sketch the curve of the function approaching the vertical asymptote [tex]\( x = -2 \)[/tex] from both sides and also approaching the horizontal asymptote [tex]\( y = 0 \)[/tex] as [tex]\( x \)[/tex] goes to positive and negative infinity.
### Final Graph
The final graph will show the behavior of the function with the vertical asymptote at [tex]\( x = -2 \)[/tex], the horizontal asymptote at [tex]\( y = 0 \)[/tex], and the plotted points correctly illustrating the function's shape.
### Step 1: Determine the Vertical Asymptote
The vertical asymptote occurs where the denominator is zero. Here, the denominator is [tex]\(-x-2\)[/tex]. Setting this equal to zero and solving for [tex]\( x \)[/tex]:
[tex]\[ -x - 2 = 0 \][/tex]
[tex]\[ -x = 2 \][/tex]
[tex]\[ x = -2 \][/tex]
So, the vertical asymptote is at [tex]\( x = -2 \)[/tex].
### Step 2: Determine the Horizontal Asymptote
For large values of [tex]\( x \)[/tex], the rational function [tex]\( f(x) \)[/tex] approaches a horizontal asymptote. As [tex]\( x \)[/tex] approaches either positive or negative infinity, the term [tex]\(-x - 2\)[/tex] grows large in magnitude, and thus [tex]\( f(x) \)[/tex] approaches zero. Hence, the horizontal asymptote is:
[tex]\[ y = 0 \][/tex]
### Step 3: Plot Points Around the Vertical Asymptote
To understand the behavior of the function around the vertical asymptote, we will plot points on either side of [tex]\( x = -2 \)[/tex].
1. Points to the left of [tex]\( x = -2 \)[/tex]:
- For [tex]\( x = -3 \)[/tex]:
[tex]\[ f(-3) = \frac{2}{-(-3) - 2} = \frac{2}{3 - 2} = \frac{2}{1} = 2 \][/tex]
So the point is [tex]\((-3, 2)\)[/tex].
- For [tex]\( x = -4 \)[/tex]:
[tex]\[ f(-4) = \frac{2}{-(-4) - 2} = \frac{2}{4 - 2} = \frac{2}{2} = 1 \][/tex]
So the point is [tex]\((-4, 1)\)[/tex].
2. Points to the right of [tex]\( x = -2 \)[/tex]:
- For [tex]\( x = -1 \)[/tex]:
[tex]\[ f(-1) = \frac{2}{-(-1) - 2} = \frac{2}{1 - 2} = \frac{2}{-1} = -2 \][/tex]
So the point is [tex]\((-1, -2)\)[/tex].
- For [tex]\( x = 0 \)[/tex]:
[tex]\[ f(0) = \frac{2}{-0 - 2} = \frac{2}{-2} = -1 \][/tex]
So the point is [tex]\((0, -1)\)[/tex].
### Step 4: Draw the Graph
1. Draw the vertical asymptote as a dashed line at [tex]\( x = -2 \)[/tex].
2. Draw the horizontal asymptote as a dashed line at [tex]\( y = 0 \)[/tex].
3. Plot the points [tex]\((-3, 2)\)[/tex] and [tex]\((-4, 1)\)[/tex] to the left of [tex]\( x = -2 \)[/tex].
4. Plot the points [tex]\((-1, -2)\)[/tex] and [tex]\((0, -1)\)[/tex] to the right of [tex]\( x = -2 \)[/tex].
5. Sketch the curve of the function approaching the vertical asymptote [tex]\( x = -2 \)[/tex] from both sides and also approaching the horizontal asymptote [tex]\( y = 0 \)[/tex] as [tex]\( x \)[/tex] goes to positive and negative infinity.
### Final Graph
The final graph will show the behavior of the function with the vertical asymptote at [tex]\( x = -2 \)[/tex], the horizontal asymptote at [tex]\( y = 0 \)[/tex], and the plotted points correctly illustrating the function's shape.
We appreciate your time on our site. Don't hesitate to return whenever you have more questions or need further clarification. Thank you for your visit. We're committed to providing you with the best information available. Return anytime for more. Thank you for choosing Westonci.ca as your information source. We look forward to your next visit.